2017
DOI: 10.1038/srep39899
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic MiR-291b-3p Mediated Glucose Metabolism by Directly Targeting p65 to Upregulate PTEN Expression

Abstract: Several studies have suggested an important role of miR-291b-3p in the development of embryonic stem cells. In previous study, we found that the expression of miR-291b-3p was significantly upregulated in the liver of db/db mice. However, the role of miR-291b-3p in glucose metabolism and its underlying mechanisms remain unknown. In the present study, we demonstrated that miR-291b-3p was abundantly expressed in the liver. Of note, hepatic miR-291b-3p expression was upregulated in HFD-fed mice and induced by fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Interestingly, miR291b was detected in both non-parenchymal cells and hepatocytes; treatment of mice with HA35 prevented these ethanol-induced increases in both cell types. While the increase in miR291b expression in non-parenchymal cells is consistent with our data from Kupffer cells after chronic ethanol feeding, induction of miR291b in hepatocytes may also be of pathophysiological significance, as miR291b-3p has been reported to induce hepatocyte apoptosis by downregulating HuR and Bcl-2 expression 28 and also impact glucose and lipid homeostasis in hepatocytes 29 , 30 . Therefore, future investigations will investigate if expression of miR291b in hepatocytes in response to ethanol exposure might play an important role in ethanol-induced hepatocyte injury.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, miR291b was detected in both non-parenchymal cells and hepatocytes; treatment of mice with HA35 prevented these ethanol-induced increases in both cell types. While the increase in miR291b expression in non-parenchymal cells is consistent with our data from Kupffer cells after chronic ethanol feeding, induction of miR291b in hepatocytes may also be of pathophysiological significance, as miR291b-3p has been reported to induce hepatocyte apoptosis by downregulating HuR and Bcl-2 expression 28 and also impact glucose and lipid homeostasis in hepatocytes 29 , 30 . Therefore, future investigations will investigate if expression of miR291b in hepatocytes in response to ethanol exposure might play an important role in ethanol-induced hepatocyte injury.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study has indicated that miR-291-3p induces liver cell apoptosis via targeting RNA binding protein HuR (19). Additionally, increased miR-291-3p expression levels led to abnormal glucose and lipid metabolism in liver cells (20,21). These data suggested that abnormal miR-291-3p level in liver cells could result in liver cell damage.…”
Section: Introductionmentioning
confidence: 82%
“…miRs are a cluster of small, non-coding RNAs. Numerous miRs have important roles in the regulation of the activation of the insulin signalling pathway, including miR-291b-3p (18), miR-200s (19), miR-152 (20), miR-20a-5p (21), miR-19a (22) and miR-301a (23). The results of our previous study suggested that miR-338-3p regulates the AKT/GSK pathway via targeting of PP4R1, which subsequently regulates protein phosphatase 4 (PP4) expression (11).…”
Section: Discussionmentioning
confidence: 99%